2013
DOI: 10.1590/s1983-14472013000200015
|View full text |Cite
|
Sign up to set email alerts
|

Percepção da equipe de enfermagem sobre humanização em unidade de tratamento intensivo neonatal e pediátrica

Abstract: The humanization of healthcare is one of the key priorities of healthcare policies in Brazil, and directly reflects on the attitudes of user, employees and managers of health services. The aim of this study was to identify perception of the nursing team in terms of humanization of assistance in a neonatal and paediatric intensive care unit based on exploratory-descriptive research and a qualitative approach. A total of 11 members of a nursing team at the neonatal and paediatric intensive care unit of a hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
41

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 10 publications
(16 reference statements)
0
7
0
41
Order By: Relevance
“…E que a partir disso, percebe-se outra forma de realizar o cuidado humanizado tanto ao paciente, quanto ao familiar. Esta forma se estende à empatia, modalidade esta, que é associa diretamente ao acolhimento (6) .…”
Section: Dificuldades Vivenciadas Pela Equipe De Enfermagemunclassified
See 1 more Smart Citation
“…E que a partir disso, percebe-se outra forma de realizar o cuidado humanizado tanto ao paciente, quanto ao familiar. Esta forma se estende à empatia, modalidade esta, que é associa diretamente ao acolhimento (6) .…”
Section: Dificuldades Vivenciadas Pela Equipe De Enfermagemunclassified
“…Logo, uma das formas de se realizar o cuidado humanizado tanto ao paciente, quanto ao familiar, e que está diretamente associada à empatia, é o acolhimento (6) .…”
Section: Introductionunclassified
“…As a source of interpretation for what is happening in life, religiosity is support for coping with difficulties and attitude change. 17 It is observed that the spiritual dimension has its relevance in the world of health, so it cannot be forgotten by care professionals, since care in other dimensions, such as spiritual, is of fundamental importance in sustaining and coping with health-disease process. 1 Care should not be restricted only to the physical structure.…”
Section: Was Very Discouraged and I Went Find This Mood To Stay Hermentioning
confidence: 99%
“…Contudo, a mortalidade e morbidade perinatal ainda persistem e são decorrentes de distúrbios ou circunstâncias superpostas ao curso normal de eventos associados com o nascimento e ajustamento à existência extrauterina [1][2][3][4] . A Unidade de Terapia Intensiva Neonatal (UTIN) configura-se como um espaço de produção de cuidado integral ao recém-nascido (RN) e à família para o controle de eventos adversos e complicações que, muitas vezes, impediam os cuidados maternos e enfatizavam a atuação da equipe de saúde durante a internação neonatal [4][5][6] . Para tanto, a integração da equipe de cuidados neonatais com a família do RN de risco torna-se relevante para a evolução do tratamento de maneira sistematizada a fim de garantir o bem estar e segurança do RN no ambiente da UTIN e promover a humanização da assistência prestada a ele e à sua família com foco na gestão da qualidade [7][8][9] .…”
Section: Introductionunclassified